The Role of Green Brand Love in Mediating Reliability, Attractiveness, and Informativeness toward Green Customer Citizenship Behavior - Pangestu, Yulia Kinanti; Kuswati, Rini (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study examines the mediating role of Green Brand Love in the relationship between Reliability, Attractiveness, and Informativity on Green Customer Citizenship Behavior. The research population consisted of students from the Faculty of Economics and Business at Universitas Muhammadiyah Surakarta and members of the general public who have purchased products or used services at Larissa Aesthetic Center. A quantitative research method was employed, utilizing a survey research design. Data was collected through Google Forms questionnaires to assess respondents' attitudes, beliefs, opinions, characteristics, and behaviors. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was used for data analysis. The findings indicate significant positive relationships between Reliability, Attractiveness, and Informativity with Green Brand Love, as well as with Green Customer Citizenship Behavior. Moreover, Green Brand Love was found to mediate the relationship between Reliability, Attractiveness, and Informativity with Green Customer Citizenship Behavior. These results underscore the importance of Green Brand Love as a mediator in influencing environmentally friendly consumer behaviors. The study contributes to understanding the interconnectedness of these variables and their impact on consumer behavior towards the environment.